Thioether complexes of WSCl4, WOCl4 and WSCl3 and evaluation of thiochloride complexes as CVD precursors for WS2 thin films. Issue 8 (5th February 2020) - Smith, Danielle E.; Greenacre, Victoria K.; Hector, Andrew L.; Huang, Ruomeng; Levason, William; Reid, Gillian; Robinson, Fred; Thomas, Shibin
Abstract : Thioether complexes of WECl4 and WECl3 (E = S, O) are prepared and characterised; the dinuclear [(WSCl4 )2 { i PrS(CH2 )2 S i Pr}] is shown to be an effective single source precursor for low pressure CVD of WS2 thin films. Abstract : The red-brown [(WSCl4 )2 {μ-RS(CH2 )2 SR}] (R = Me, Ph, i Pr) and [(WSCl4 )2 {μ-MeS(CH2 )3 SMe}] have been made by reaction of WSCl4 with the thioether in a 2 : 1 molar ratio, in anhydrous CH2 Cl2 solution, and characterised by microanalysis, IR, UV/Vis and 1 H NMR spectroscopy. The X-ray structures of the four dithioether complexes reveal square pyramidal WSCl4 units and bridging dithioethers with WS trans to thioether sulfur. Paramagnetic W(v ) complexes, [WSCl3 {RS(CH2 )2 SR}] (R = Me, i Pr), have been made similarly using a 1 : ≥1 ratio of reactants or longer reaction times. The W(vi ) complexes, [WSCl4 (SMe2 )] and [WSCl4 (SeMe2 )], are also described. Analogous complexes of WOCl4, [(WOCl4 )2 {RS(CH2 )2 SR}] (R = Ph, i Pr), have been made similarly from WOCl4, but reactions using MeS(CH2 ) n SMe ( n = 2, 3) led to reduction to W(v ), forming [WOCl3 {MeS(CH2 ) n SMe], both of which were identified crystallographically. Curiously, they are geometric isomers: [WOCl3 {MeS(CH2 )3 SMe}] has the dithioether trans Cl/Cl whereas in [WOCl3 {MeS(CH2 )2 SMe}] it is trans O/Cl. Remarkably, low pressure chemical vapour deposition (CVD) experiments using the dinuclear W(vi ) species, [(WSCl4 )2 { i PrS(CH2 )2 S i Pr}], as a single source precursor produced thin films of 4H-WS2, identified by grazing incidence X-ray diffraction, scanning electron microscopy, X-ray photoelectron spectroscopy and Raman spectroscopy; the tungsten thiochloride complex is the first single source low pressure CVD precursor for WS2 . In contrast, the mononuclear W(v ) complex, [WSCl3 { i PrS(CH2 )2 S i Pr}], does not deposit WS2 under similar conditions.